Perceptions on stress and academic performance among students-residents of barangay Palaca, Miag-ao, Iloilo - Quilantang, Ma. Ellaine N.
This correlational study amed to determine the relationship between perception on stress and academic performance among students-residents of Barangay Palaca, Miagao, Iloilo. Thirty (30) students-residents (11 males and 19 females) of Barangay Palaca, Miagao, Iloilo participated in the study. Perception on stress was measured usng the 10-item Perceived Stress Scale. Perception on academic performance was measured using a 10-item-scale constructed by the researcher. The mean, standard deviation, and Pearson r correlation Coeffecient were utilized to interpret the data. The results of the study revealed that high level of stress was perceived with a mean score (x) of 46.67 and standard deviation (Sd) of -9.36. Low level of stress was perceived with a mean score (x) of 36.67 and a standard deviation (Sd) of 2.07). Good perception on academic performance, on the other hand, got a mean score (x) of 60.40 and a standard deviation (Sd) of 3.64. Contrary to what was hypothesized, perception on stress and academic performance was negatively correlated with a correlation coefficient score of 0.27.